Efficacy of Sodium Hypochlorite (NaOCl) Against Gram Positive and Gram Negative Bacteria: A Systematic Literature Review - Jeli Marlita; Yuyun Febriani; Baiq Risma Fatmayanti; Leny Ramadhan (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Sodium hypochlorite (NaOCl) is a chemical compound that acts as a strong oxidizer commonly used as an antibacterial, antiseptic, and disinfectant in various pharmaceutical and health applications. This systematic review aims to evaluate the antibacterial activity of NaOCl against various types of bacteria based on the PICO framework. Literature searches were conducted through the PubMed, ScienceDirect, and Scopus databases for publications from 2017 to 2024. Inclusion criteria included all types of bacteria, the use of NaOCl as an antibacterial or antimicrobial agent, and articles published within that time frame. The interventions reviewed were the use of NaOCl at various concentrations, while the control group referred to conditions without treatment or a comparative antibacterial agent. The results were determined based on antimicrobial activity against the bacteria tested. Two stages of independent literature searches were conducted according to the established inclusion and exclusion criteria. This review shows that NaOCl has significant antibacterial activity against various bacteria, with effectiveness depending on the concentration and characteristics of the target microorganisms.